(untitled) (Research, Society and Development, 2022)
Among the primary malignant tumors of childhood, retinoblastoma stands out, a very common primary eye neoplasm in this age group. However, it is considered a challenge for developing countries, since the diagnosis ends up being late due to socioeconomic and demographic factors. This study aims to identify the main signs and symptoms of retinoblastoma, determine the mean time between the onset of symptoms and diagnosis; and to assess the main complications associated with delayed diagnosis of retinoblastoma. For this, an integrative literature review of an exploratory and descriptive nature with a qualitative approach was carried out in the PubMed and ScienceDirect databases, through the selection of full available articles, published between 2012 and 2022, in English and Portuguese. From this, 12 articles were selected that meet the inclusion and exclusion criteria of the present study, to compose the present study. These articles showed that with the early diagnosis of retinoblastoma, cure rates increase and vision is preserved in a large number of patients, minimizing treatment and maximizing quality of life.